INNOVATIVE DIRECTIONS FOR IMPROVING THE MECHANISMS FOR ADVANCED TRAINING OF TEACHING STAFF IN NON-STATE EDUCATIONAL ORGANIZATIONS - Azam Shakhriyorovich Kholmurodov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, an analysis of the organizational and pedagogical conditions for the processes of advanced training of teachers in non-state educational organizations, problems that negatively affect the effectiveness of advanced training processes, improvement of the organizational and pedagogical mechanisms for advanced training of teachers in non-state educational organizations, as well as the mentioned innovative model for improving the efficiency of advanced training processes in non-state educational organizations.